2019
DOI: 10.3390/admsci9020035
|View full text |Cite
|
Sign up to set email alerts
|

The Quality of Entrepreneurial Activity and Economic Competitiveness in European Union Countries: A Panel Data Approach

Abstract: To increase competitiveness, a country has to outperform its competitors in terms of research and innovation, entrepreneurship, competition, and education. In this paper, we aim to test the relationship between the quality of entrepreneurial activity and the economic competitiveness for the European Union countries by using panel data estimation techniques. Our research considers a sample of 28 EU countries over the period 2011–2017. For the empirical investigation we apply panel data regression models. The re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
1
3

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(24 citation statements)
references
References 61 publications
0
14
1
3
Order By: Relevance
“…No studies were found that relate these two variables. However, some authors indicate that there is a negative relationship between high job creation expectations and economic competitiveness [72,73].…”
Section: Discussion Of the Results Of The Linear Regression Equation mentioning
confidence: 99%
“…No studies were found that relate these two variables. However, some authors indicate that there is a negative relationship between high job creation expectations and economic competitiveness [72,73].…”
Section: Discussion Of the Results Of The Linear Regression Equation mentioning
confidence: 99%
“…The authors explored how the selected HDI, ESHDI and EPI indexes reflect developments in the cyclical economy, which has only recently become one of the approaches to achieving sustainable development and is primarily linked to its economic and environmental aspects. The importance of multicriterial analysis in the context of increasing the countries' economic prosperity was also confirmed by Rusu and Dornean (2019). The authors were focused on investigating the selected economic areas such as competitiveness, innovations, and macroeconomic environment.…”
Section: Literature Reviewmentioning
confidence: 94%
“…This means that potential re-entrepreneurs respond differently because the opportunity cost of those that are not employed (by necessity) differs from those that are exploring a new business opportunity (by opportunity). The quality of entrepreneurship is a relevant factor that explains the growth of a country's competitiveness (Cardon et al 2011;Guerrero and Peña-Legazkue 2019;Henrekson and Sanandaji 2019;Rusu and Dornean 2019). On the other hand, environmental conditions also determine the re-entry speed after a business failure (Guerrero and Peña-Legazkue 2019).…”
Section: Proposed Conceptual Model and Propositionsmentioning
confidence: 99%
“…As a consequence, the type their entrepreneurial initiatives also vary depending on social capital (Cope 2011;Henrekson and Sanandaji 2019). The quality and the speed of a new venture depends on the entrepreneur's relationships with family (Khelil 2016;Lin and Wang 2019), potential investors (Henrekson and Sanandaji 2019), mentors, and agents of entrepreneurial ecosystems (Rusu and Dornean 2019). Social partners also contribute with elements for an accelerated/retarded re-entry (Baù et al 2017).…”
Section: Proposed Conceptual Model and Propositionsmentioning
confidence: 99%